Novel use of contegra valved conduits in idiopathic bilateral brachiocephalic vein stenosis - Suraj Wasudeo Nagre; Krishnarao Narayanrao Bhosle (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
Thromboses of the upper limp and neck veins are rare in comparison with those of the lower extremities. Innominate Vein Thrombosis (IVT) is an elusive vascular disease that is rarely seen, with potentially lethal complications such as sepsis and pulmonary embolism. It is usually secondary to intravenous drug abuse, prolonged central venous catheterization or deep head-neck infections or trauma. The history and examination in patients with an IVT may be vague and misleading. Patients may present with a painful swelling of the neck but they may also be absolutely asymptomatic.  Initial medical treatment of the patients includes thrombolytic, anticoagulant and steroid drug therapies. If the patient's symptoms do not improve with medication, surgical or endovascular interventions are performed. The indications for open, surgical revascularization are rare and usually reserved for patients whose symptoms are refractory to anticoagulation and endovascular treatment. We report successful decompression of severe venous hypertension of head, neck, face and bilateral upper limb of a 39 year old male patient having symptoms such as facial, neck and bilateral shoulder intermittent edema, occasional dyspnea, chest pain, and headache since 1 year. CT Venography s/o bilateral brachiocephalic vein [Innominate vein] and left subclavin vein stenosis. After all investigations for searching cause of thrombosis all reports normal, nothing found so we called it as idiopathic. We used two contegra valved bovine conduits. Proximal end of the first contegra valve conduit was anastamosed to right distal IJV and distal end to the SVC. The another contegra graft's proximal end was anastamosed to the left distal IJV and distal end to the first contegra graft distal to its valve. It provided promt and effective venous outflow, with complete resolution of the venous engorgement over the face and upper limb, and also a patent graft six months postoperatively.